Charlotte Bronte and Srpuhi Dussap: weaver mothers and palimpsest as grammer of female narration and plot - Aktokmakyan, Maral. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The use of double-talk becomes the female discourse in Charlotte Brontë’s Jane Eyre and Srpuhi Dussap’s Mayda. This method as female literary strategy, also termed the style of palimpsest, gives the woman writer the opportunity to tell/ write whatever she likes, thinks and believes and at the same time avoid male criticism and reduction. As nineteenth century writers, both Brontë and Dussap constructed their novels in styles which seem to comply with conventional plots, themes and literary rules. The striking characteristic of both novels is the subversion of the apparent obedience they advocate through similar plots and thematic alternatives they offer. Only in this way is woman’s self-fulfilment achieved and she is promoted as a subject as opposed to her imprisonment in the role of the object. This study aims to discuss the reasons for their application of the palimpsest and the way they are applied in Jane Eyre and Mayda.